Pengaruh Media Interaktif Wordwall terhadap Kemampuan Pemahaman Konsep Matematis Siswa Madrasah Tsanawiyah Manba’ul Ulum Dasan Ketujur, Lombok Barat - Rahmawati, Rahmawati; Arvy, Baiq Rofina Arvy (Jurnal of Math Tadris, 2025)
This article aims to test the effect of using Wordwall media on students' mathematical concept understanding ability at MTs Manba'ul Ulum Dasan Ketujur. This study uses a quantitative approach of quasi-experimental type with post-test only control group design. The population in this study were all female students of class VIII consisting of two classes, namely class VIII-1 students totaling 22 students as the control class, and class VIII-2 totaling 22 students as the experimental class. The sampling technique used a saturated sampling technique involving all members of the population as research samples. Data were collected through tests and observations. The results of this study indicate that the Sig. (2-tailed) value in the independent sample t-test is 0.002 <0.05 which indicates that H_0 is rejected, so it can be concluded that there is an effect of Wordwall learning media on students' mathematical concept understanding ability at Madrasah Tsanawiyah.